2002
DOI: 10.1029/2001jd000707
|View full text |Cite
|
Sign up to set email alerts
|

Balloon‐borne observations of water vapor and ozone in the tropical upper troposphere and lower stratosphere

Abstract: Balloon‐borne observations of frost‐point temperature and ozone in the equatorial western, central and eastern Pacific as well as over equatorial eastern Brazil provide a highly accurate data set of water vapor across the tropical tropopause. Data were obtained at San Cristóbal, Galapagos, Ecuador (0.9°S, 89.6°W), during the late northern winter and the late northern summer in 1998 and 1999 and at Juazeiro do Norte, Brazil (7.2°S, 39.3°W), in February and November 1997. Earlier data in the western Pacific regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 53 publications
4
112
1
1
Order By: Relevance
“…SOWER has been using the NOAA/CMDL frostpoint hygrometer (FPH) between 1998 and 2002 (Vömel et al, 2002) and the University of Colorado Cryogenic Frostpoint Hygrometer (CFH) since 2003 . It has also been flying the Snow White (SW) hygrometers since the year 2000, and has flown nearly 100 sondes.…”
Section: Analysis Of the Water Vapor Sonde Datamentioning
confidence: 99%
“…SOWER has been using the NOAA/CMDL frostpoint hygrometer (FPH) between 1998 and 2002 (Vömel et al, 2002) and the University of Colorado Cryogenic Frostpoint Hygrometer (CFH) since 2003 . It has also been flying the Snow White (SW) hygrometers since the year 2000, and has flown nearly 100 sondes.…”
Section: Analysis Of the Water Vapor Sonde Datamentioning
confidence: 99%
“…They showed that this maximum was related to the uplifting of surface emissions by convective processes. These studies and others (e.g., Vömel et al, 2002) show that the TTL is characterized by a specific air composition, in particular during the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…The main airborne experiments were the TROPOZ II (Tropospheric Ozone) experiment that took place in January 1991 (Marenco et al, 1995) and the TRACE A (Transport and Atmospheric Chemistry Near the Equator-Atlantic) experiment that took place during the dry (September/October) and the wet (April) seasons in 1992 (Fishman et al, 1996). In parallel, balloon-borne instruments were flown in Central and Eastern Brazil mainly performing measurements of ozone (Kirchhoff et al, 1996;Logan, 1999;Pundt et al, 2002;Vömel et al, 2002;Thompson et al, 2003). One of the most outstanding results from these observational studies was, that there is a large increase of the ozone mixing ratio with altitude starting in the UT well below the tropopause (Logan, 1999;Pundt et al, 2002;Thompson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1998 the Soundings of Ozone and Water in the Equatorial Region (SOWER)/Pacific mission has been conducted on a campaign basis at San Cristóbal, Galá pagos, Ecuador (0.9 S, 89.6 W) and Christmas Island, Kiribati (2.0 N, 157.5 W) supplementing the on-going program at Watukosek, Indonesia (7.5 S, 112.6 E). Results from these campaigns have been contributing to the understanding of stratospheretroposphere exchange (e.g., Fujiwara et al 2001;Vömel et al 2002) and to the equatorial tropospheric ozone distribution which will be described in this paper.…”
Section: Introductionmentioning
confidence: 99%